Occupational Health and Safety (OHS) Cost Measures for the Sweepers at Jashore and Benapole Paurashava in Bangladesh - Kabir, Sardar Lutful (Universitas Airlangga, 2023)
Background: Jashore, the oldest and Benapole, a new municipality in Bangladesh which total area is 32 square km having 0.6 million people including 516 enlisted cleaners. They are living with limited services, though the National Policy on OHS was formulated which summarizes the existing policies, laws, and guidelines in the country. Methods: Respondents were selected through homogeneous sampling method. They were directly interviewed and provided their data which was analyzed using secondary data. Objectives: To find out the monthly health and safety cost of a sweeper and how much additional cost they will agree to spend to ensure their occupational health and safety. Results: Their income sources are restricted, which is average 12187 BDT and expenditure is around 12679 BDT monthly. They do not have any savings options or any insurance for their financial security. Their profession as well as the health and safety issues are not secured by any authorities. Considering the types of profession, 18% are doing septic tank cleaning, 21% doing pit latrine cleaning and 61% are doing both. Findings: Study shows only 7% respondents use PPE set at the time of toilet/drain cleaning and 30% nothing used. But reality is, almost all know about the benefits of using PPE. The consequences for not following safety measures were about 25% suffered accidental injury and 28% of their family were affected by skin disease. For precautionary and treatment purpose, they need to spend an additional 8% of their monthly income. Conclusion: This study sought to offer recommendations on how PPE would be more usable, respondents positively responded. Traditional manual profession is reducing day by day and it has been increasing the vulnerable situation of the sweeper community. The priority is reducing, and they are considering it as a secondary profession.